Legal Framework for Integrating Crop and Livestock Farming with Sus-tainable Development in Indonesian Laws - isharyanto; Deva Mahendra Caesar Bimantya (Faculty of Law-Universitas Bandar Lampung, 2025)
This article analyzes the legal framework governing crop-livestock integration in Indonesia and it’s alignment with sustainable development principles. Although the Food Law, the Livestock and Animal Health Law, and the Evironmental Protection and Management Law recognize sustainability and the use of local resources, they don’t provide operational guidance for integrating crops and livestock. The research finds regulatory fragmentation: livestock manure is legally treated as waste rather than a soil nutrient, forage production is not mandated within livestock enterprises, and extension services operate under separate sectoral structures. Comparative analysis of Malaysia, Thailand, and India demonstrates that successful integration that support nutrient cycling and smallholder autonomy. This research purposes three core elements for legal reform: recognizing livestock manure as an agricultural resource, requiring forage production plans, and unifying agricultural extension under a single village-level farming plan. Strengthening these provisions would create a cohesive legal basis for sustainable crop-livestock systems and reinforce food security for smallholder farmers.